Definitive chemoradiotherapy versus neoadjuvant chemoradiotherapy and esophagectomy for the treatment of esophageal and gastroesophageal carcinoma – A systematic review and meta-analysis. (December 2021) - Chow, Ronald; Murdy, Kyle; Vaska, Marcus; Lee, Sangjune Laurence
Highlights: MEDLINE (Ovid), EMBASE, and Cochrane Central Register of Controlled Trials were searched from database initiation (1946 for MEDLINE, 1974 for EMBASE, and 1995 for Cochrane) up until May 2021. Eight studies were included in this review. Patients receiving neoadjuvant chemoradiotherapy with esophagectomy had better overall survival – HR 0.55; 95% CI: 0.49–0.62. Toxicity was similar, between the two treatments. Given the paucity of data and lack of uniform reporting of endpoints, further studies should be conducted. Abstract: Introduction: There currently exists limited data comparing definitive chemoradiotherapy to neoadjuvant chemoradiotherapy with esophagectomy for patients with esophageal carcinoma. While we await more trials, we conducted a systematic review and meta-analysis of randomized controlled trials and observational studies with either propensity score matched or multivariable analyses, to provide a better understanding of the relative efficacy and effectiveness. Methods: MEDLINE (Ovid), EMBASE, and Cochrane Central Register of Controlled Trials were searched from database initiation (1946 for MEDLINE, 1974 for EMBASE, and 1995 for Cochrane) up until May 2021. Articles were included if they reported on overall survival or toxicity data. Summary hazard ratio (HR) and 95% confidence interval (CI) was calculated using a random-effects DerSimonian-Laird model. Results: Eight studies with a total of 16, 647 patients were included in this review. Patients receiving neoadjuvant chemoradiotherapy with esophagectomy had better overall survival – HR 0.55; 95% CI: 0.49–0.62. Toxicity was similar, between the two treatments. Conclusion: Patients with esophageal carcinoma receiving neoadjuvant chemoradiotherapy and esophagectomy have better survival than patients receiving definitive chemoradiotherapy. Given the paucity of data and lack of uniform reporting of endpoints, further studies should be conducted.